2016
DOI: 10.1080/14656566.2016.1225725
|View full text |Cite
|
Sign up to set email alerts
|

Sonidegib for the treatment of advanced basal cell carcinoma

Abstract: Introduction. Advanced and metastatic basal cell carcinomas (BCCs) are rare but still

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…A 42-month analysis of the randomized BOLT study confirmed the long-term efficacy and safety of sonidegib; the objective response rate (ORR) observed for patients with locally advanced basal cell carcinoma (laBCC) was 56.1% (95% CI 43.3-68.3%) and 46.1% (95% CI 37.2-55.1) for the 200 mg and 800 mg groups, respectively.…”
Section: Key Summary Pointsmentioning
confidence: 87%
See 1 more Smart Citation
“…A 42-month analysis of the randomized BOLT study confirmed the long-term efficacy and safety of sonidegib; the objective response rate (ORR) observed for patients with locally advanced basal cell carcinoma (laBCC) was 56.1% (95% CI 43.3-68.3%) and 46.1% (95% CI 37.2-55.1) for the 200 mg and 800 mg groups, respectively.…”
Section: Key Summary Pointsmentioning
confidence: 87%
“…Side effects from SMO inhibitors are very common and can be significant. Adverse events frequently represent a limiting factor in continuous treatment, and dose adjustments or different schemes to avoid discontinuation and increase patients compliance are often required [45,46]. In the initial BOLT study, [22].…”
Section: Safety Tolerability and Adverse Eventsmentioning
confidence: 99%
“…Vismodegib is the first FDA-approved SMO inhibitor [13], in 2012, for the treatment of basal cell carcinoma and has been subsequently studied against colon [14], pancreatic [15], and medulloblasto-ma tumors [16]. In patients suffering from resistance to treatment [17][18][19][20], sonidegib, the second inhibitor of SMO approved by the FDA in 2015 [21], is used [22][23][24]. Other possible inhibitors against SMO, subjected to research, and possibly used in resistance to vismodegib and sonidegib [25], are natural products such as chalcone 12 [26], analogs of vitamin D3 [27], or itraconazole, the new inhibitor that might act against mutated SMO [28].…”
Section: Resultsmentioning
confidence: 99%
“…During the follow‐up of patients with advanced BCC treated with HPI, discussing treatment and informing about possible adverse events to expect is of key importance (Table ). Sonidegib should be taken at least 2 hours after a meal and at least 1 hour before the following meal . The absorption of vismodegib is not affected by food .…”
Section: Follow‐up Of Patients During Hpi Treatment For Adverse Eventsmentioning
confidence: 99%